How hydrogen sulfide deposition from oil exploitation may affect bacterial communities and the health of forest soils in Congolese coastal plains? - Koutika, Lydie-Stella (Frontiers in Soil Science, 2022)
The hydrogen sulfide (H2S) deposition from oil exploitation occurring since 1969 may potentially affect bacterial communities in acacia and eucalyptus plantations of the Congolese coastal plains. These plantations have been implemented on previous native savannas to use the unsuitable soils for agriculture, provide pulp wood and fuel wood energy, and preserve the natural forests. Increased carbon (C) and nitrogen (N) stocks in stands containing acacia relative to baseline (eucalyptus) stocks have been reported. Phosphorus availability also improved in coarse particulate organic matter (4,000–250 µm) in afforested stands as compared to natural savannas. Investigation of the abundance of bacterial phyla by metabarcoding of the 16S rRNA bacterial gene in different stands of monocultures and mixed-species stands reveals the prevalence of Actinobacteria in all stands. This phylum is generally associated with the presence of sulfur in industrial areas and has a crucial role in organic matter decomposition. This may be linked to improved soil attributes (C, N, and P) and related to oil exploitation in addition to natural processes. This review shows, therefore, how potentially human activities may impact bacterial community composition, which may further change other soil attributes. It also acknowledges that the sustainability of forest plantations on inherently nutrient-poor soils strongly relies on interactions between soil functions, the environment, and human activities driven by soil organisms.